Work and family: possibilities for integration - Bilac, Elisabete Doria [UNESP] (Univ Sao Paolo, Dept Sociologia, 2014)
This article explores work-family integration, taking into account, on one hand, the way in which this discussion has transformed conceptually over time since the 1970s and, on the other, the empirical observation of the persistence of a model based on overburdening women and relatively low male participation in reproduction. The text discusses the extent to which this persistence derives from a specific combination of demographic and socioeconomic elements and the failure of the few work-family integration policies existing in Brazil to provide widespread access.
Keywords: Domestic work; Care; Decline in fertility; Aging population; Female participation in the care work market